Efek Impresi Fintech Terhadap Perilaku Keuangan Usaha Kecil Menegah (UKM) - Gendro Wiyono; Kusuma Chandra Kirana (UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA, 2020)
The purpose of this study was to determine the Impression of finance technology (Fintech) in the form of benefits as well as theeasy to use that has an impact on SME intentions to use it, even though problems in its implementation are indicated. The sample used was 80 SMEs spread in the Special Region of Yogyakarta. Data collection using purposive sampling technique provided that the respondents chosen already use fintech. Data analysis using SmartPLS software. The results showed that the benefits of fintech had a positive and significant effect on the financial behavior of SMEs to intend to use it. The more the benefits increase, the behavior of using fintech is growing. It is human's rational nature that what is beneficial to him will encourage behavior. The impression of ease of use of fintech has no positive and significant effect. It is generally known that the attitude towards computer use is a significant determinant of the intention to use fintech. However, the impression of simplicity did not encourage the intention to utilize fintech. Although fintech is perceived as easy, if the benefits are low, UKM does not intend to use it. The implemantation problem has not been proven to have an effect on preventing SMEs from using fintech. Public awareness of the importance of security has not been considered, this is because the community has never felt the impression of the impact of cyber risk. That the problem of fintech implementation is realized is a risk that has a negative effect on the intention of adopting fintech. However, the problems that arise do not reduce the interest of SMEs to use fintech.